PENGARUH ASET PAJAK TANGGUHAN DAN BEBAN PAJAK TANGGUHAN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2022 - Tambunan, Cristin Octavia; Saragih, Joana L. (UNIKA Santo Thomas, 2024)
This study aims to research and discuss whether or not there is an influence of deferred tax assets and deferred tax expenses on earnings management with the object of research being property and real estate companies listed on the Indonesia Stock Exchange in the 2019-2022 period. In this research, data is used using annual financial report data obtained from the site www.idx.com. By using a purposive sampling technique, 13 companies were obtained which were used as the final sample in this research. The analytical method used in this research uses the Multiple Linear Regression Analysis method. This research shows that deferred tax assets have a positive and significant effect on earnings management. This can be seen from the partial test that has been carried out where Tcount > Ttable (2.367 > 1.66088) with a significance of 0.020 < 0.05 and deferred tax expense has a positive and significant effect on earnings management. This can be seen from the spatial test that has been carried out where Tcount > Ttable (8.616 > 1.66088) with a significance of 0.000 < 0.05. The coefficient of determination of the independent variables deferred tax assets and deferred tax expense on the dependent variable earnings management is 51.8%.